PENGEMBANGAN APLIKASI PEMBELAJARAN MY SOLAR SYSTEM PADA MATERI BUMI DAN TATA SURYA - Fatmawati, Sulis; Hadi, Wiwin Puspita; Sidik, Rahmad Fajar; Wahyuni, Eva Ari; Wulandari, Ana Yuniasti Retno (Program Studi Pendidikan IPA, Universitas Trunojoyo Madura, 2025)
This study aims to determine the feasibility, response, media readability, and students' understanding of Nature of Science. This type of research is a pure development with the ADDIE development model (Analyze, Design, Develop, Implement, and Evaluate). The research was conducted at Kanzul Ulum Junior High School grade VII with a total of 27 students for the 2023-2024 school year. The research instrument used a validation questionnaire of media experts, material experts, responses, readability, and Nature of Science comprehension tests. Based on the research, conclusions were obtained: (1) The results of material feasibility and media feasibility obtained a score of 1 with very valid criteria (2) The results of students' responses in individual trials 86.71%, small group trials 84.37% with very good criteria. Meanwhile, the large group test 77.83% with good criteria (3) The results of media readability in the individual trial 87.29%, the small group trial 85.88% with very good criteria.